A synergistic interaction between HDAC‐ and PARP inhibitors in childhood tumors with chromothripsis. Issue 4 (28th April 2022) - Khalid, Umar; Simovic, Milena; Hammann, Linda A.; Iskar, Murat; Wong, John K. L.; Kumar, Rithu; Jugold, Manfred; Sill, Martin; Bolkestein, Michiel; Kolb, Thorsten; Hergt, Michaela; Devens, Frauke; et al.
Abstract: Chromothripsis is a form of genomic instability characterized by the occurrence of tens to hundreds of clustered DNA double‐strand breaks in a one‐off catastrophic event. Rearrangements associated with chromothripsis are detectable in numerous tumor entities and linked with poor prognosis in some of these, such as Sonic Hedgehog medulloblastoma, neuroblastoma and osteosarcoma. Hence, there is a need for therapeutic strategies eliminating tumor cells with chromothripsis. Defects in DNA double‐strand break repair, and in particular homologous recombination repair, have been linked with chromothripsis. Targeting DNA repair deficiencies by synthetic lethality approaches, we performed a synergy screen using drug libraries (n = 375 compounds, 15 models) combined with either a PARP inhibitor or cisplatin. This revealed a synergistic interaction between the HDAC inhibitor romidepsin and PARP inhibition. Functional assays, transcriptome analyses and in vivo validation in patient‐derived xenograft mouse models confirmed the efficacy of the combinatorial treatment. Abstract : What's new? Chromothripsis is a type of genomic instability in which hundreds of chromosomal rearrangements occur at once. In certain tumor types, including medulloblastoma, neuroblastoma and osteosarcoma, chromothripsis is associated with poor prognosis. Here, the authors screened for drug pairs that target and kill tumor cells with chromothripsis while sparing cells that have functional DNA repair. Their screen uncovered a strong synergistic interaction between the HDAC inhibitor romidepsin and PARP inhibitors. Combination therapy worked well to stop tumor growth and induce apoptosis in patient‐derived xenografts.